Yield and antiyield genes in common bean (Phaseolus vulgaris L.). Issue 3 (31st March 2021) - Reinprecht, Yarmilla; Qi, Yanzhou; Shahmir, Fariba; Smith, Thomas H.; Pauls, Karl Peter
Abstract: High yield is the primary criterion for the development of new cultivars at the University of Guelph common bean breeding program. As a complex trait, yield is encoded by a number of genes contributing minor effects while also being significantly affected by environmental factors. Genes that increase yield with fixed resources have their effects by increasing input use efficiency. When suppressed, the BnMicEmUP gene has a positive effect on seed production in Arabidopsis . Preliminary work has shown that ortholog of this gene ( Phvul.009G190100 ) exists in common bean, and its expression was negatively correlated with yield in a field test of 10 navy bean cultivars with different yield potentials. The aim of this research was to characterize the Phvul.009G190100 gene and to develop gene‐based marker(s) to test for alleles associated with high yield in common bean. A database search identified a second yield‐related gene ( Phvul.009G202100 ) on the same chromosome (Pv09), which is a homolog to Phvul.009G190100 . Both genes contain a DUF1118 protein domain, which has the molecular characteristics of a basic leucine zipper (bZIP) transcription factor, based on in silico analysis. Temperature switch polymerase chain reaction (PCR) markers, which were developed for both genes, were significantly associated with yield and maturity in 42 bean genotypes belonging to different market classes. The work will benefit bean breeding programs by making them more efficient in selecting high yielding cultivars, and it will directly benefit bean producers through accelerated access to new, high yielding cultivars.